CURRENT PROBLEMS OF HISTORY TEACHING IN UZBEKISTAN AND THEORIES OF THE DEVELOPMENT OF THE SCIENCE - Azimova Shokhista Salohiddinovna (American Journals Publishing, 2024)
From time immemorial, our country has been an integral part of world civilization, a single geographical region, from the migration of various tribes at different stages of history, the emergence of the first city-states in this region to our modern statehood, and many historical events: wars and massacres, the Islamic Renaissance, the decline of states and khanates from flourishing empires, have taken an indelible place in the pages of our history.
Keywords: History, students-youth, ancient times, the Middle Ages, modern history, source studies, state and society.